2019
DOI: 10.1111/are.14252
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of temperature and live feed period on growth and survival of Coregonus maraena (Bloch, 1779) larvae

Abstract: Despite intensive stocking programmes, wild Maraena whitefish Coregonus maraena (Bloch, 1779)-stocks are in danger of extinction in the Baltic sea region. Current aquaculture rearing methods in recirculating aquaculture systems (RAS) are lacking efficient protocols for transitioning larvae from endogenous to exogenous feeding. In this 34-day-experiment the offspring of wild fish was used. Maraena whitefish larvae were weaned at three different temperatures (15.9°C, 17.9°C, 19.7°C) and three feeding regimes, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…The survival rate of the most successful group in the present study (FW15) was higher than other reported results (Beltran & Champigneulle, 1992;Bochert & Luft, 2019;Leithner & Wanzenbock, 2015) for a comparable length trial. Ostaszewska et al (2018) reported considerably lower survival at the end of a 35-day experiment (82.9%) for a feeding strategy similar to FW15 in the present study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The survival rate of the most successful group in the present study (FW15) was higher than other reported results (Beltran & Champigneulle, 1992;Bochert & Luft, 2019;Leithner & Wanzenbock, 2015) for a comparable length trial. Ostaszewska et al (2018) reported considerably lower survival at the end of a 35-day experiment (82.9%) for a feeding strategy similar to FW15 in the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…This was also observed by Mahmoudzadeh, Ahmadi, and Shamsaei (2009), who reported that larvae fed dry feed showed comparable SR to those fed a live and a live/artificial mixed diet during the first 4 weeks. Bochert and Luft (2019) found superior survival in C. maraena larvae fed exclusively with dry feed compared to those receiving Artemia and a mixture of live and dry feed from the initiation of exogenous feeding, irrespective culture temperature (6–20°C). A similar feeding technique with Artemia only for the first phase of rearing, followed by a cofeeding 50% Artemia and 50% dry feed and a final transition to dry feed only, is used in Atlantic whitefish Coregonus huntsmanui as described in a rearing handbook (Whitelaw et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The maraena whitefish (Coregonus maraena, Bloch, 1779), like the well-studied rainbow trout (Oncorhynchus mykiss, Walbaum, 1792), belongs to the salmonids and is an ecologically important species in the Baltic Sea region [31]. Maraena whitefish, which spawns mainly in estuaries, were brought to the edge of extinction in the 20th century.…”
Section: Introductionmentioning
confidence: 99%
“…Maraena whitefish is a species-rich genus of mostly cold-water benthivores that grow optimally at water temperatures between 13 and 18°C like it is found in the Baltic Sea [ 5 ]. Today this fish is also kept in aquaculture [ 6 , 7 ]. The aim on the one side is to replenish the natural stocks of the Baltic Sea.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, both species used in this study were bred in an aquaculture facility and well adapted to the local conditions of the Baltic Sea [ 6 ]. In a former study, the physical meat quality of both species was compared [ 24 ].…”
Section: Introductionmentioning
confidence: 99%